IR spectroscopy, thermal characterization and X-ray diffraction of Cd microparticles doped PLA/PHA composite films - Pekdemir, Mustafa Ersin; Pekdemir, Sibel Selçuk; Kavum, Ahmet; Altun, Sedanur (Niyazi BULUT, 2024)
In this study, shape-memory and biodegradable poly lactic acid (PLA) and poly hydroxy alkanoate (PHA) were mixed in a 1:1 ratio and films were obtained by solvent casting method. Then, cadmium (Cd) microparticles were added to the PLA/PHA blend at different rates and the composite films were prepared using the same method. PLA/PHA/Cd composite films were characterized by Attenuated Total Reflection-Infrared (ATR-IR) spectroscopy, Thermogravimetric analysis (TGA), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). Finally, in the study, the crystallinity values obtained from the XRD patterns of the pure blend film and the composite films were compared.
Keywords: Physical Chemistry (Other); Fiziksel Kimya (Diğer)